Dinasti Politik Di Indonesia Dalam Perspektif Fiqh Siyasah - Syacharani Aulia Fachri; Noprisa Sumantri, Sonya; Adelia Ningsih, Febri; Sabrina, Shafiyah; Sukry Daulay, Ahmad; Rahayu Pratiwi (Tabayyun : Journal Of Islamic Studies, 2025)
Islam does not havei ai completei and prei-eixisting political or governmental system, including discussions about political dynasties. Thei phenomenon of politicail dynaistieis occurreid in thei history of Islaim, ais weill ais in Indoneisiai, during thei reformerai, its scopei expanded from regional to national levels. Indeed, therei is no policy that prohibits political dynasties in Indonesiai from implementing it, but if this situation continues, it can threaten thei existencei of thei Indonesian government and damagei thei essence of democracy. This study aiims to explain how the practice of political dynasties existed in Indonesia during thei reformera and explain how contemporary Islamic jurisprudence views, in this case using thei ideology of Muhammaid Abid Al-Jabiri's political essay, the practice of political dynasties in Indonesiai. Thei research method used in this study is library research, using normativei, historical, and sociological approaches. Thei analysis technique of this study uses content analysis. The results of this study indicatei that the practice of political dynasties in Indonesiai raises many different problems, ranging from politics to economics. The development of political dynasties in Indonesia is also influenced by several factors, including the absence of policies that prohibit political dynasty activities, and others. In the practice of political dynasties in Indonesiai, faith is interpreted as political ideology, ethnicity as nepotism and ghanimah as economic interests, whether the economic interests of the political dynasty or others.